Melogonimus rhodanometra n. g., n. sp. (Digenea: Ptychogonimidae) from the elasmobranch Rhina ancylostoma Bloch & Schneider (Rhinobatidae) from the southeastern coastal waters of Queensland, Australia - Bray, R. A.; Brockerhoff, A.; Cribb, T. H. (Systematic Parasitology, 1995)
The new genus Melogonimus is defined and adults of its type-species, M. rhodanometra n. sp., are described from Rhina ancylostoma from Moreton Bay, Queensland. This is the first record of a digenean from this host species. It is argued that metacercariae from the portunid crab Portunus pelagicus from Hervey Bay, off Queensland, belong to M. rhodanometra. The definition of the family Ptychogonimidae is amended, and a key to its two genera is given. Melogonimus is characterised by a smooth genital atrium wall, a large sinus-organ, a large muscular seminal vesicle, a weakly developed pars prostatica, a pre-testicular uterus and confluent post-testicular vitelline fields.